Glucose sensing and homeostasis by adipocyte GPCR - Hasan, Nazmul; Chhabra, Kavaljit H. (Frontiers in Endocrinology, 2025)
The adipose tissue regulates energy homeostasis, which is one of the vital processes for organismal survival, and its dysregulation causes metabolic diseases including obesity and type 2 diabetes. Glucose is utilized by the adipose tissue for energy production and storage to regulate systemic glucose homeostasis. The G-protein-coupled receptors (GPCRs) expressed in the adipose tissues play a crucial role in adipocyte function by responding to hormonal, neural, and metabolic signals; thereby, influencing insulin sensitivity, glucose uptake and lipid metabolism. The specific contribution of adipocyte GPCRs to glucose sensing and its utilization is incompletely understood. Therefore, in this review we explore the diverse molecular and integrative mechanisms through which GPCR signaling in the adipose tissue senses glucose to regulate systemic glucose homeostasis. We first discuss the major GPCR families that modulate intracellular second messenger cascades in response to glucose and nutrient availability in the adipose tissue, and their metabolic implications in pathophysiological conditions like obesity and diabetes. These GPCRs regulate glucose sensing, lipid metabolism, adipokine secretion, and thereby coordinating metabolic responses with other central and peripheral tissues including the brain, pancreas, intestine and liver. Subsequently, we review the molecular mechanisms through which the adipocyte GPCR regulates systemic glucose homeostasis, from glucose sensing to its utilization. Determining how the GPCRs in the adipose tissue sense glucose will offer new and better therapeutic approaches for treating metabolic diseases including diabetes and obesity.